Optogenetic techniques for the study of native potassium channels - Sandoz, Guillaume E.; Levitz, Joshua (Frontiers in Molecular Neuroscience, 2013)
Optogenetic tools were originally designed to target specific neurons for remote control of their activity by light and have largely been built around opsin-based channels and pumps. These naturally photosensitive opsins are microbial in origin and are unable to mimic the properties of native neuronal receptors and channels. Over the last 8 years, photoswitchable-tethered ligands (PTLs) have enabled fast and reversible control of mammalian ion channels, allowing optical control of neuronal activity. One such PTL, MAQ, contains a maleimide (M) to tether the molecule to a genetically engineered cysteine, a photoisomerizable azobenzene (A) linker and a pore-blocking quaternary ammonium group (Q). MAQ was originally used to photo-control SPARK, an engineered light-gated potassium channel derived from Shaker. Potassium channel photo-block by MAQ has recently been extended to a diverse set of mammalian potassium channels including channels in the voltage-gated and K2P families. Photoswitchable potassium channels, which maintain native properties, pave the way for the optical control of specific aspects of neuronal function and for high precision probing of a specific channel’s physiological functions. To extend optical control to natively expressed channels, without overexpression, one possibility is to develop a knock-in mouse in which the wild type channel gene is replaced by its light-gated version. Alternatively, the recently developed photoswitchable-conditional-subunit technique (PCS) provides photocontrol of the channel of interest by molecular replacement of wild type complexes. Finally, photochromic ligands (PCLs) also allow photocontrol of potassium channels without genetic manipulation using soluble compounds. In this review we discuss different techniques for optical control of native potassium channels and their associated advantages and disadvantages.